Highly conductive corrosion-resistant bipolar lead-acid battery substrate and method of making same
Patent Information
- Application Number
- CN202611460922.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-23
AI Technical Summary
本发明的目的在于提供一种高导电耐腐蚀双极性铅蓄电池基板及其制备方法,以解决现有基板导电性偏低、耐硫酸腐蚀性不足、界面结合可靠性差以及机械强度不够的问题
(1)本发明通过对Ti4O7进行硅烷偶联剂表面活化、聚苯胺包覆和二氧化硅包覆,在Ti4O7表面依次构建了偶联剂锚固层、导电中间层和耐腐蚀外层。硅烷偶联剂在酸性醇水溶液中水解生成硅羟基,与Ti4O7表面羟基缩合形成Si-O-金属键,使偶联剂分子以化学键形式锚固于Ti4O7表面,同时引入有机官能团,使Ti4O7由亲水表面转变为亲油表面,改善了其与聚偏氟乙烯基体的相容性,有利于降低填料团聚倾向。聚苯胺通过苯胺单体在Ti4O7表面原位化学氧化聚合形成包覆层,聚苯胺主链为共轭结构,电子可沿共轭链迁移,且其在硫酸电解液中可发生质子酸掺杂,电导率进一步提高,聚苯胺包覆层在Ti4O7颗粒之间的接触处提供导电通路,降低了颗粒间的接触电阻,同时改善了Ti4O7颗粒在聚偏氟乙烯基体中的分散性,有利于形成完善的导电网络。二氧化硅包覆层由正硅酸乙酯在碱性醇水溶液中水解缩合生成的二氧化硅沉积于聚苯胺层表面而形成,二氧化硅在硫酸中化学性质稳定,可阻隔硫酸对聚苯胺层和Ti4O7内核的侵蚀,同时二氧化硅表面丰富的硅羟基与改性聚偏氟乙烯侧链的氨基形成氢键或在硫酸环境中形成离子键,增强了涂层与芯层的界面结合力。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lead-acid battery technology, specifically to a highly conductive and corrosion-resistant bipolar lead-acid battery substrate and its preparation method. Background Technology
[0002] In the field of electrochemical energy storage, bipolar lead-acid batteries have attracted widespread attention due to their compact structure, low internal resistance, and high power density. The core component of a bipolar lead-acid battery is the bipolar substrate. One side of this substrate serves as the carrier for the positive electrode active material, and the other side serves as the carrier for the negative electrode active material. Simultaneously, it must effectively isolate the electrolyte between adjacent individual cells and efficiently conduct electrons. Therefore, the bipolar substrate material must possess excellent conductivity, resistance to strong acid corrosion, airtightness to the electrolyte, and sufficient mechanical strength.
[0003] In existing technologies, the material selection for bipolar lead-acid battery substrates mainly falls into two categories. One category consists of metallic substrates, represented by pure lead or lead alloys. Pure lead substrates offer good chemical stability but suffer from high density and weight, which is detrimental to improving battery energy density. While lead alloys can improve mechanical strength, in sulfuric acid media, alloying elements are prone to selective corrosion or passivation, leading to increased internal resistance and affecting the battery's high-current discharge performance and cycle life. The other category comprises composite substrates filled with carbon materials or conductive fillers and thermoplastic polymers. These materials are lightweight but face the challenges of high potential and strong oxidation environment on the positive electrode side. Ordinary carbon materials are prone to electrochemical oxidation corrosion at the positive electrode potential, while the polymer matrix and conductive fillers are only physically bonded, resulting in micro-defects at the interface. Sulfuric acid easily penetrates along the interface, leading to decreased substrate conductivity and structural damage.
[0004] In recent years, researchers have attempted to improve the corrosion resistance of composite substrates by replacing traditional carbon materials with conductive ceramic materials, and by adding acid-resistant polymers to enhance the overall protective capability of the substrates. However, the uniformity of the dispersion of conductive ceramic powder in the polymer matrix and the interfacial bonding strength between the powder and the matrix remain difficult to guarantee. During long-term operation, the filler is prone to delamination from the matrix, affecting the stability of the substrate. Therefore, how to simultaneously improve the conductivity, corrosion resistance, and interfacial bonding reliability of composite substrates has become a pressing technical problem to be solved in this field. Summary of the Invention
[0005] (a) Technical problems to be solved The purpose of this invention is to provide a highly conductive and corrosion-resistant bipolar lead-acid battery substrate and its preparation method, so as to solve the problems of low conductivity, insufficient resistance to sulfuric acid corrosion, poor interfacial bonding reliability and insufficient mechanical strength of existing substrates.
[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: A highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes a core layer and a conductive and corrosion-resistant coating covering the surface of the core layer.
[0007] Furthermore, the core layer is composed of the following raw materials in parts by weight: 40-60 parts modified polyvinylidene fluoride, 15-30 parts graphite, 10-20 parts conductive carbon black, and 5-10 parts barium sulfate.
[0008] Furthermore, the conductive anti-corrosion coating is composed of the following raw materials in parts by weight: 30-50 parts modified polyvinylidene fluoride, 20-40 parts modified conductive ceramic powder, and 5-15 parts conductive carbon black.
[0009] Furthermore, the modified conductive ceramic powder is prepared by surface activation of Ti4O7 with silane coupling agent, polyaniline coating, and silica coating.
[0010] Furthermore, the modified polyvinylidene fluoride is prepared by grafting acrylic acid onto polyvinylidene fluoride via electron beam pre-irradiation, amidation reaction, and nitro reduction reaction.
[0011] Furthermore, the modified conductive ceramic powder is prepared by the following steps: A1. Add Ti4O7 to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, wherein the ratio of Ti4O7 to ethanol solution is 1:(8~15)g / mL, adjust the pH to 4-5 with acetic acid, ultrasonically disperse for 10-30 min, stir and react at 50-70℃ for 2-4 h, filter, wash with anhydrous ethanol, and vacuum dry at 80-100℃ for 4-8 h to obtain surface-activated conductive ceramic powder; A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, wherein the ratio of the surface-activated conductive ceramic powder to the hydrochloric acid solution containing aniline monomer is 1:(10~30)g / mL. The dispersion is ultrasonically dispersed for 10-30 min, stirred at 0-5℃ for 30-60 min, and then ammonium persulfate hydrochloric acid solution is slowly added dropwise over a period of 30-60 min. After the addition is complete, the reaction is continued at 0-5℃ for 4-8 h. The mixture is then filtered and washed with deionized water until neutral to obtain polyaniline-coated conductive ceramic powder. A3. Disperse the polyaniline-coated conductive ceramic powder in an ethanol solution, wherein the ratio of the polyaniline-coated conductive ceramic powder to the ethanol solution is 1:(10~25)g / mL. Adjust the pH to 8-9 with ammonia water, stir at 40-60℃, and simultaneously add anhydrous ethanol solution of tetraethyl orthosilicate dropwise over 30-60 min. After the addition is complete, continue the reaction for 4-8 h. Filter, wash alternately with deionized water and anhydrous ethanol, and vacuum dry at 60-80℃ for 8-12 h to obtain modified conductive ceramic powder.
[0012] Furthermore, in step A1, the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 1-3 wt% for γ-glycidoxypropyltrimethoxysilane, and the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of (7-10):1.
[0013] Furthermore, in step A2, the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.05-0.2 mol / L, and the concentration of hydrochloric acid is 0.8-1.2 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.05-0.2 mol / L; and the molar ratio of ammonium persulfate to aniline is (0.8~1):1.
[0014] Furthermore, in step A3, the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of (3~5):1; the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution of tetraethyl orthosilicate is 1:(3~8); and the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is (0.05~0.15):1.
[0015] Furthermore, the modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder is pre-irradiated in a nitrogen atmosphere using an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder is transferred to a methanol solution of acrylic acid. The ratio of the pre-irradiated polyvinylidene fluoride powder to the methanol solution of acrylic acid is 1:(5~15) g / mL. The reaction is carried out at 60-80℃ for 2-6 hours under nitrogen protection. The mixture is then filtered, washed alternately with methanol and deionized water, and vacuum dried at 60-80℃ for 8-12 hours to obtain acrylic acid-grafted polyvinylidene fluoride. B2. Dissolve the acrylic acid-grafted polyvinylidene fluoride in dry N-methylpyrrolidone, wherein the ratio of the acrylic acid-grafted polyvinylidene fluoride to the N-methylpyrrolidone is 1:(8~20) g / mL. Add N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide, and stir at room temperature for 30-60 min under nitrogen protection. Add p-nitroaniline, and react at 40-60℃ for 8-16 h under nitrogen protection. Precipitate by dropping the reaction solution into methanol, filter, wash with methanol, and vacuum dry at 60-80℃ for 8-12 h to obtain the amidated intermediate product. B3. Disperse the amidation intermediate in tetrahydrofuran, wherein the ratio of the amidation intermediate to the tetrahydrofuran is 1:(6~15)g / mL, add hydrazine hydrate, and react at 50-70℃ for 4-8h under nitrogen protection. Filter, wash alternately with deionized water and ethanol until neutral, and vacuum dry at 60-80℃ for 12-24h to obtain modified polyvinylidene fluoride.
[0016] Furthermore, in step B1, the absorbed dose of the pre-irradiation treatment is 40-60 kGy, and the dose rate is 5-20 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 15-25 wt%.
[0017] Furthermore, in step B2, the amount of N,N'-dicyclohexylcarbodiimide added is 2-10 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 1-5 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 3-12 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride.
[0018] Furthermore, in step B3, the mass ratio of the hydrazine hydrate to the amidation intermediate is (0.5~2):1.
[0019] A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes the following steps: S1. Place the modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate in a mixer and stir and mix at 500-1000 rpm for 20-40 minutes at room temperature to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 180-195℃ and 10-20MPa for 30-60 minutes. After cooling and demolding, the core layer is obtained. S3. Place modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, wherein the total mass of the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black is in the ratio of N-methylpyrrolidone to 1:(3~8)g / mL, and stir and disperse at 500-800rpm for 30-60min to obtain a conductive anti-corrosion coating slurry; S4. The conductive and anti-corrosion coating slurry is uniformly coated on the surface of the core layer, with a coating thickness of 100-250μm. It is dried at 80-120℃ for 1-3 hours and then cooled to obtain a highly conductive and corrosion-resistant bipolar lead-acid battery substrate.
[0020] (iii) Beneficial technical effects Compared with the prior art, the beneficial effects of the present invention are: (1) This invention constructs a coupling agent anchoring layer, a conductive intermediate layer, and a corrosion-resistant outer layer on the surface of Ti4O7 by surface activation with a silane coupling agent, polyaniline coating, and silica coating. The silane coupling agent hydrolyzes in an acidic alcohol aqueous solution to generate silanol groups, which condense with the hydroxyl groups on the Ti4O7 surface to form Si-O-metallic bonds, thus anchoring the coupling agent molecules to the Ti4O7 surface in the form of chemical bonds. At the same time, organic functional groups are introduced, which changes the Ti4O7 surface from hydrophilic to oleophilic, improving its compatibility with polyvinylidene fluoride and helping to reduce the tendency of filler agglomeration. Polyaniline is formed by in-situ chemical oxidation polymerization of aniline monomers on the surface of Ti4O7 to create a coating layer. The polyaniline backbone has a conjugated structure, allowing electrons to migrate along the conjugated chains. Furthermore, it can undergo protonic acid doping in sulfuric acid electrolyte, further improving conductivity. The polyaniline coating layer provides conductive pathways at the contact points between Ti4O7 particles, reducing interparticle contact resistance and improving the dispersion of Ti4O7 particles in polyvinylidene fluoride (PVDF), thus facilitating the formation of a complete conductive network. The silica coating layer is formed by depositing silica, generated from the hydrolysis and condensation of tetraethyl orthosilicate in an alkaline alcoholic aqueous solution, onto the surface of the polyaniline layer. Silica is chemically stable in sulfuric acid, preventing its erosion of the polyaniline layer and the Ti4O7 core. Simultaneously, the abundant silanol groups on the silica surface form hydrogen bonds with the amino groups of the modified PVDF side chains or ionic bonds in the sulfuric acid environment, enhancing the interfacial adhesion between the coating and the core layer.
[0021] (2) This invention introduces amino functional groups at the end of the side chains of polyvinylidene fluoride (PVDF) through electron beam pre-irradiation grafting with acrylic acid, amidation, and nitro reduction. Electron beam irradiation causes homolytic cleavage of the CH bonds on the PVDF molecular chain, generating macromolecular free radicals. These macromolecular free radicals, upon contact with the acrylic acid monomer, initiate a graft polymerization reaction, grafting the polyacrylic acid side chains onto the PVDF backbone, thereby introducing carboxyl groups. In the amidation reaction, the carboxyl groups generate an active ester intermediate under the action of N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide. The active ester reacts with the amino group of p-nitroaniline to form an amide bond, attaching the p-nitrophenyl group to the PVDF side chain. In the nitro reduction reaction, hydrazine hydrate selectively reduces the nitro group to an amino group, ultimately forming an amino group at the end of the PVDF side chain. In a sulfuric acid electrolyte environment, amino groups can be protonated to form ammonium cations, which then form hydrogen bonds and ionic bonds with the silanol groups on the Ti4O7 surface or the amino groups on the polyaniline chains. This enhances the interfacial bonding between the polymer matrix and the conductive filler, and reduces the channels through which sulfuric acid penetrates along interfacial defects.
[0022] (3) This invention combines modified conductive ceramic powder with modified polyvinylidene fluoride (PVDF), uses graphite and conductive carbon black as auxiliary conductive components, and barium sulfate as reinforcing filler to construct a composite structure of a core layer with a complete conductive network and a dense interface. The main chain of PVDF is a carbon-fluorine structure with high CF bond energy, which gives the material good resistance to sulfuric acid corrosion and thermal stability. A dense core layer can be obtained by hot pressing, and a firmly bonded conductive and anti-corrosion coating can be formed on the surface of the core layer by solution coating. The core layer and the coating use a homogeneous polymer matrix. During the coating process, the solvent contained in the slurry causes micro-swelling on the surface of the core layer. After drying, the polymer molecular chains of the two layers interpenetrate and entangle, further enhancing the reliability of the interface bonding.
[0023] (4) The substrate of this invention adopts a polymer composite material system, which has a significant lightweight advantage compared with pure lead plates or lead alloy plates. The lamellar morphology of Ti4O7 forms a stacked arrangement in the coating, which prolongs the penetration path of the corrosive medium and forms a multidimensional conductive network with conductive carbon black and graphite. The resulting substrate has a low corrosion rate in sulfuric acid environment, while maintaining good conductivity and mechanical strength, which is beneficial to improving the power density and service life of bipolar lead-acid batteries. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1 A highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes a core layer and a conductive and anti-corrosion coating covering the surface of the core layer; wherein the core layer is composed of the following raw materials in parts by weight: 40 parts modified polyvinylidene fluoride, 15 parts graphite, 10 parts conductive carbon black, and 5 parts barium sulfate; the conductive and anti-corrosion coating is composed of the following raw materials in parts by weight: 30 parts modified polyvinylidene fluoride, 20 parts modified conductive ceramic powder, and 5 parts conductive carbon black.
[0026] The modified conductive ceramic powder is prepared by the following steps: A1. Ti4O7 was added to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, the pH was adjusted to 4 with acetic acid, ultrasonically dispersed for 10 min, stirred at 50 °C for 4 h, filtered, washed with anhydrous ethanol, and vacuum dried at 80 °C for 8 h to obtain surface-activated conductive ceramic powder. The ratio of Ti4O7 to ethanol solution is 1:8 g / mL; the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 1 wt% for γ-glycidoxypropyltrimethoxysilane, and the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 7:1. A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, ultrasonically dispersed for 10 min, stirred at 0℃ for 60 min, and then ammonium persulfate hydrochloric acid solution is slowly added dropwise over a period of 60 min. After the addition is complete, the reaction is continued at 0℃ for 8 h. The mixture is then filtered and washed with deionized water until neutral to obtain polyaniline-coated conductive ceramic powder. The ratio of the surface-activated conductive ceramic powder to the hydrochloric acid solution containing aniline monomer is 1:10 g / mL; the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.05 mol / L, and the concentration of hydrochloric acid is 0.8 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.05 mol / L; and the molar ratio of ammonium persulfate to aniline is 0.8:1. A3. The polyaniline-coated conductive ceramic powder is dispersed in an ethanol solution, the pH is adjusted to 8 with ammonia, and the mixture is stirred at 40°C while an anhydrous ethanol solution of tetraethyl orthosilicate is added dropwise over a period of 60 min. After the addition is complete, the reaction continues for 8 h. The mixture is then filtered, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 60°C for 12 h to obtain the modified conductive ceramic powder. The ratio of the polyaniline-coated conductive ceramic powder to the ethanol solution is 1:10 g / mL; the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 3:1; the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution of tetraethyl orthosilicate is 1:3; and the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is 0.05:1.
[0027] The modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder was pre-irradiated in a nitrogen atmosphere by an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder was transferred to a methanol solution of acrylic acid and reacted at 60°C for 6 hours under nitrogen protection. After filtration, the powder was washed alternately with methanol and deionized water and dried under vacuum at 60°C for 12 hours to obtain acrylic acid-grafted polyvinylidene fluoride. The absorbed dose of the pre-irradiation treatment is 40 kGy, and the dose rate is 5 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 15 wt%; the ratio of the pre-irradiated polyvinylidene fluoride powder to the methanol solution of acrylic acid is 1:5 g / mL. B2. The acrylic acid-grafted polyvinylidene fluoride was dissolved in dry N-methylpyrrolidone, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide were added, and the mixture was stirred at room temperature for 30 min under nitrogen protection. p-Nitroaniline was added, and the mixture was reacted at 40 °C for 16 h under nitrogen protection. The reaction solution was dropped into methanol to precipitate the product, filtered, washed with methanol, and dried under vacuum at 60 °C for 12 h to obtain the amidated intermediate product. The ratio of acrylic acid-grafted polyvinylidene fluoride to N-methylpyrrolidone is 1:8 g / mL; the amount of N,N'-dicyclohexylcarbodiimide added is 2 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 1 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 3 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride. B3. The amidation intermediate was dispersed in tetrahydrofuran, hydrazine hydrate was added, and the reaction was carried out at 50°C for 8 h under nitrogen protection. The mixture was filtered, washed alternately with deionized water and ethanol until neutral, and dried under vacuum at 60°C for 24 h to obtain modified polyvinylidene fluoride. The ratio of the amidation intermediate to the tetrahydrofuran is 1:6 g / mL; the mass ratio of the hydrazine hydrate to the amidation intermediate is 0.5:1.
[0028] A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes the following steps: S1. Modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate are placed in a mixer and stirred at 500 rpm for 40 minutes at room temperature to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 180°C and 10MPa for 60 minutes. After cooling and demolding, the core layer is obtained. S3. Place the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, and stir and disperse at 500 rpm for 60 min to obtain a conductive anti-corrosion coating slurry. The ratio of the total mass of the modified polyvinylidene fluoride, the modified conductive ceramic powder, and the conductive carbon black to the N-methylpyrrolidone is 1:3 g / mL. S4. The conductive and anti-corrosion coating slurry is uniformly coated on the surface of the core layer with a coating thickness of 100 μm. After drying at 80°C for 3 hours and cooling, a highly conductive and corrosion-resistant bipolar lead-acid battery substrate is obtained.
[0029] Example 2 A highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes a core layer and a conductive and anti-corrosion coating covering the surface of the core layer; wherein the core layer is composed of the following raw materials in parts by weight: 45 parts modified polyvinylidene fluoride, 19 parts graphite, 12 parts conductive carbon black, and 6 parts barium sulfate; the conductive and anti-corrosion coating is composed of the following raw materials in parts by weight: 35 parts modified polyvinylidene fluoride, 25 parts modified conductive ceramic powder, and 8 parts conductive carbon black.
[0030] The modified conductive ceramic powder is prepared by the following steps: A1. Ti4O7 was added to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, the pH was adjusted to 4.2 with acetic acid, ultrasonically dispersed for 15 min, stirred at 55 °C for 3.5 h, filtered, washed with anhydrous ethanol, and vacuum dried at 85 °C for 7 h to obtain surface-activated conductive ceramic powder. The ratio of Ti4O7 to ethanol solution is 1:10 g / mL; the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 1.5 wt% for γ-glycidoxypropyltrimethoxysilane, and the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 8:1. A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, ultrasonically dispersed for 15 min, stirred at 1°C for 45 min, and then ammonium persulfate hydrochloric acid solution is slowly added dropwise over a period of 45 min. After the addition is complete, the reaction continues at 1°C for 7 h. The mixture is then filtered and washed with deionized water until neutral to obtain polyaniline-coated conductive ceramic powder. The ratio of the surface-activated conductive ceramic powder to the hydrochloric acid solution containing aniline monomer is 1:15 g / mL; the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.09 mol / L, and the concentration of hydrochloric acid is 0.9 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.09 mol / L; and the molar ratio of ammonium persulfate to aniline is 0.85:1. A3. The polyaniline-coated conductive ceramic powder was dispersed in an ethanol solution, the pH was adjusted to 8.2 with ammonia, and the mixture was stirred at 45°C while an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise over a period of 45 min. After the addition was complete, the reaction was continued for 7 h. The mixture was then filtered, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 65°C for 11 h to obtain the modified conductive ceramic powder. The ratio of the polyaniline-coated conductive ceramic powder to the ethanol solution is 1:14 g / mL; the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 3.5:1; the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution is 1:4; and the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is 0.08:1.
[0031] The modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder was pre-irradiated in a nitrogen atmosphere by an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder was transferred to a methanol solution of acrylic acid and reacted at 65°C for 5 hours under nitrogen protection. After filtration, the powder was washed alternately with methanol and deionized water and dried under vacuum at 65°C for 11 hours to obtain acrylic acid-grafted polyvinylidene fluoride. The absorbed dose of the pre-irradiation treatment is 45 kGy, and the dose rate is 9 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 17.5 wt%; the ratio of the pre-irradiated polyvinylidene fluoride powder to the methanol solution of acrylic acid is 1:8 g / mL. B2. The acrylic acid-grafted polyvinylidene fluoride was dissolved in dry N-methylpyrrolidone, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide were added, and the mixture was stirred at room temperature for 40 min under nitrogen protection. p-Nitroaniline was added, and the mixture was reacted at 45 °C for 14 h under nitrogen protection. The reaction solution was dropped into methanol to precipitate the product, filtered, washed with methanol, and dried under vacuum at 65 °C for 11 h to obtain the amidated intermediate product. The ratio of the acrylic acid-grafted polyvinylidene fluoride to the N-methylpyrrolidone is 1:11 g / mL; the amount of N,N'-dicyclohexylcarbodiimide added is 4 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 2 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 5 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride. B3. The amidation intermediate was dispersed in tetrahydrofuran, hydrazine hydrate was added, and the reaction was carried out at 55°C for 7 h under nitrogen protection. The mixture was filtered, washed alternately with deionized water and ethanol until neutral, and dried under vacuum at 65°C for 21 h to obtain modified polyvinylidene fluoride. The ratio of the amidation intermediate to the tetrahydrofuran is 1:8 g / mL; the mass ratio of the hydrazine hydrate to the amidation intermediate is 0.9:1.
[0032] A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes the following steps: S1. Modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate are placed in a mixer and stirred at 600 rpm for 25 minutes at room temperature to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 184°C and 13MPa for 53 minutes. After cooling and demolding, the core layer is obtained. S3. Place the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, and stir and disperse at 575 rpm for 45 min to obtain a conductive anti-corrosion coating slurry. The ratio of the total mass of the modified polyvinylidene fluoride, the modified conductive ceramic powder, and the conductive carbon black to the N-methylpyrrolidone is 1:4 g / mL. S4. The conductive anti-corrosion coating slurry is uniformly coated on the surface of the core layer with a coating thickness of 140 μm. It is dried at 90°C for 2.5 h and then cooled to obtain a highly conductive and corrosion-resistant bipolar lead-acid battery substrate.
[0033] Example 3 A highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes a core layer and a conductive and anti-corrosion coating covering the surface of the core layer; wherein the core layer is composed of the following raw materials in parts by weight: 50 parts modified polyvinylidene fluoride, 22 parts graphite, 15 parts conductive carbon black, and 7 parts barium sulfate; the conductive and anti-corrosion coating is composed of the following raw materials in parts by weight: 40 parts modified polyvinylidene fluoride, 30 parts modified conductive ceramic powder, and 10 parts conductive carbon black.
[0034] The modified conductive ceramic powder is prepared by the following steps: A1. Ti4O7 was added to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, the pH was adjusted to 4.5 with acetic acid, ultrasonically dispersed for 20 min, stirred at 60 °C for 3 h, filtered, washed with anhydrous ethanol, and vacuum dried at 90 °C for 6 h to obtain surface-activated conductive ceramic powder. The ratio of Ti4O7 to ethanol solution is 1:12 g / mL; the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 2wt% for γ-glycidoxypropyltrimethoxysilane, and the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 9:1. A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, ultrasonically dispersed for 20 min, stirred at 2.5℃ for 45 min, and then ammonium persulfate hydrochloric acid solution is slowly added dropwise over a period of 45 min. After the addition is complete, the reaction continues at 2.5℃ for 6 h. The mixture is then filtered and washed with deionized water until neutral to obtain polyaniline-coated conductive ceramic powder. The ratio of the surface-activated conductive ceramic powder to the hydrochloric acid solution containing aniline monomer is 1:20 g / mL; the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.125 mol / L, and the concentration of hydrochloric acid is 1.0 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.125 mol / L; and the molar ratio of ammonium persulfate to aniline is 0.9:1. A3. The polyaniline-coated conductive ceramic powder was dispersed in an ethanol solution, the pH was adjusted to 8.5 with ammonia, and the mixture was stirred at 50°C while an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise over a period of 45 min. After the addition was complete, the reaction was continued for 6 h. The mixture was then filtered, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 70°C for 10 h to obtain the modified conductive ceramic powder. The ratio of the polyaniline-coated conductive ceramic powder to the ethanol solution is 1:18 g / mL; the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 4:1; the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution is 1:5.5; and the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is 0.10:1.
[0035] The modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder was pre-irradiated in a nitrogen atmosphere by an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder was transferred to a methanol solution of acrylic acid and reacted at 70°C for 4 hours under nitrogen protection. After filtration, the powder was washed alternately with methanol and deionized water and dried under vacuum at 70°C for 10 hours to obtain acrylic acid-grafted polyvinylidene fluoride. The absorbed dose of the pre-irradiation treatment is 50 kGy, and the dose rate is 12 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 20 wt%; the ratio of the pre-irradiated polyvinylidene fluoride powder to the methanol solution of acrylic acid is 1:10 g / mL. B2. The acrylic acid-grafted polyvinylidene fluoride was dissolved in dry N-methylpyrrolidone, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide were added, and the mixture was stirred at room temperature for 45 min under nitrogen protection. p-Nitroaniline was added, and the mixture was reacted at 50 °C for 12 h under nitrogen protection. The reaction solution was dropped into methanol to precipitate, filtered, washed with methanol, and dried under vacuum at 70 °C for 10 h to obtain the amidated intermediate product. The ratio of acrylic acid-grafted polyvinylidene fluoride to N-methylpyrrolidone is 1:14 g / mL; the amount of N,N'-dicyclohexylcarbodiimide added is 6 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 3 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 7.5 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride. B3. The amidation intermediate was dispersed in tetrahydrofuran, hydrazine hydrate was added, and the reaction was carried out at 60°C for 6 hours under nitrogen protection. The mixture was filtered, washed alternately with deionized water and ethanol until neutral, and dried under vacuum at 70°C for 18 hours to obtain modified polyvinylidene fluoride. The ratio of the amidation intermediate to the tetrahydrofuran is 1:10.5 g / mL; the mass ratio of the hydrazine hydrate to the amidation intermediate is 1.25:1.
[0036] A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes the following steps: S1. Modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate are placed in a mixer and stirred at 750 rpm for 30 minutes at room temperature to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 188°C and 15MPa for 45 minutes. After cooling and demolding, the core layer is obtained. S3. Place the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, and stir and disperse at 650 rpm for 45 min to obtain a conductive anti-corrosion coating slurry. The ratio of the total mass of the modified polyvinylidene fluoride, the modified conductive ceramic powder, and the conductive carbon black to the N-methylpyrrolidone is 1:5.5 g / mL. S4. The conductive anti-corrosion coating slurry is uniformly coated on the surface of the core layer with a coating thickness of 175μm. It is dried at 100℃ for 2h and then cooled to obtain a highly conductive and corrosion-resistant bipolar lead-acid battery substrate.
[0037] Example 4 A highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes a core layer and a conductive and anti-corrosion coating covering the surface of the core layer; wherein the core layer is composed of the following raw materials in parts by weight: 55 parts modified polyvinylidene fluoride, 26 parts graphite, 18 parts conductive carbon black, and 9 parts barium sulfate; the conductive and anti-corrosion coating is composed of the following raw materials in parts by weight: 45 parts modified polyvinylidene fluoride, 35 parts modified conductive ceramic powder, and 12 parts conductive carbon black.
[0038] The modified conductive ceramic powder is prepared by the following steps: A1. Ti4O7 was added to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, the pH was adjusted to 4.7 with acetic acid, ultrasonically dispersed for 25 min, stirred at 65 °C for 2.5 h, filtered, washed with anhydrous ethanol, and vacuum dried at 95 °C for 5 h to obtain surface-activated conductive ceramic powder. The ratio of Ti4O7 to ethanol solution is 1:13 g / mL; the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 2.5 wt% for γ-glycidoxypropyltrimethoxysilane, and the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 9.5:1. A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, ultrasonically dispersed for 25 min, stirred at 4°C for 35 min, and then ammonium persulfate hydrochloric acid solution is slowly added dropwise over a period of 35 min. After the addition is complete, the reaction is continued at 4°C for 5 h. The mixture is then filtered and washed with deionized water until neutral to obtain polyaniline-coated conductive ceramic powder. The ratio of the surface-activated conductive ceramic powder to the hydrochloric acid solution containing aniline monomer is 1:25 g / mL; the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.16 mol / L, and the concentration of hydrochloric acid is 1.1 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.16 mol / L; and the molar ratio of ammonium persulfate to aniline is 0.95:1. A3. The polyaniline-coated conductive ceramic powder was dispersed in an ethanol solution, the pH was adjusted to 8.7 with ammonia, and the mixture was stirred at 55°C while an anhydrous ethanol solution of tetraethyl orthosilicate was added dropwise over a period of 35 min. After the addition was complete, the reaction was continued for 5 h. The mixture was then filtered, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 75°C for 9 h to obtain the modified conductive ceramic powder. The ratio of the polyaniline-coated conductive ceramic powder to the ethanol solution is 1:21 g / mL; the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 4.5:1; the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution is 1:7; and the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is 0.13:1.
[0039] The modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder was pre-irradiated in a nitrogen atmosphere by an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder was transferred to a methanol solution of acrylic acid and reacted at 75°C for 3 hours under nitrogen protection. The mixture was then filtered, washed alternately with methanol and deionized water, and dried under vacuum at 75°C for 9 hours to obtain acrylic acid-grafted polyvinylidene fluoride. The absorbed dose of the pre-irradiation treatment is 55 kGy, and the dose rate is 16 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 22.5 wt%; the ratio of the pre-irradiated polyvinylidene fluoride powder to the methanol solution of acrylic acid is 1:13 g / mL. B2. The acrylic acid-grafted polyvinylidene fluoride was dissolved in dry N-methylpyrrolidone, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide were added, and the mixture was stirred at room temperature for 50 min under nitrogen protection. p-Nitroaniline was added, and the mixture was reacted at 55 °C for 10 h under nitrogen protection. The reaction solution was dropped into methanol to precipitate the product, filtered, washed with methanol, and dried under vacuum at 75 °C for 9 h to obtain the amidated intermediate product. The ratio of the acrylic acid-grafted polyvinylidene fluoride to the N-methylpyrrolidone is 1:17 g / mL; the amount of N,N'-dicyclohexylcarbodiimide added is 8 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 4 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 10 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride. B3. The amidation intermediate was dispersed in tetrahydrofuran, hydrazine hydrate was added, and the reaction was carried out at 65°C for 5 h under nitrogen protection. The mixture was filtered, washed alternately with deionized water and ethanol until neutral, and dried under vacuum at 75°C for 15 h to obtain modified polyvinylidene fluoride. The ratio of the amidation intermediate to the tetrahydrofuran is 1:13 g / mL; the mass ratio of the hydrazine hydrate to the amidation intermediate is 1.6:1.
[0040] A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes the following steps: S1. Modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate are placed in a mixer and stirred at 900 rpm for 35 minutes at room temperature to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 192°C and 18MPa for 38 minutes. After cooling and demolding, the core layer is obtained. S3. Place the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, and stir and disperse at 725 rpm for 52 min to obtain a conductive anti-corrosion coating slurry. The ratio of the total mass of the modified polyvinylidene fluoride, the modified conductive ceramic powder, and the conductive carbon black to the N-methylpyrrolidone is 1:7 g / mL. S4. The conductive and anti-corrosion coating slurry is uniformly coated on the surface of the core layer with a coating thickness of 210 μm. After drying at 110°C for 1.5 h and cooling, a highly conductive and corrosion-resistant bipolar lead-acid battery substrate is obtained.
[0041] Example 5 A highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes a core layer and a conductive and anti-corrosion coating covering the surface of the core layer; wherein the core layer is composed of the following raw materials in parts by weight: 60 parts modified polyvinylidene fluoride, 30 parts graphite, 20 parts conductive carbon black, and 10 parts barium sulfate; the conductive and anti-corrosion coating is composed of the following raw materials in parts by weight: 50 parts modified polyvinylidene fluoride, 40 parts modified conductive ceramic powder, and 15 parts conductive carbon black.
[0042] The modified conductive ceramic powder is prepared by the following steps: A1. Ti4O7 was added to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, the pH was adjusted to 5 with acetic acid, ultrasonically dispersed for 30 min, stirred at 70 °C for 2 h, filtered, washed with anhydrous ethanol, and vacuum dried at 100 °C for 4 h to obtain surface-activated conductive ceramic powder. The ratio of Ti4O7 to ethanol solution is 1:15 g / mL; the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 3 wt% for γ-glycidoxypropyltrimethoxysilane, and the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 10:1. A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, ultrasonically dispersed for 30 min, stirred at 5°C for 30 min, and then slowly added dropwise in a hydrochloric acid solution containing ammonium persulfate over a period of 30 min. After the addition is complete, the reaction continues at 5°C for 4 h. The mixture is then filtered and washed with deionized water until neutral to obtain polyaniline-coated conductive ceramic powder. The ratio of the surface-activated conductive ceramic powder to the hydrochloric acid solution containing aniline monomer is 1:30 g / mL; the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.2 mol / L, and the concentration of hydrochloric acid is 1.2 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.2 mol / L; and the molar ratio of ammonium persulfate to aniline is 1:1. A3. The polyaniline-coated conductive ceramic powder is dispersed in an ethanol solution, the pH is adjusted to 9 with ammonia, and the mixture is stirred at 60°C while an anhydrous ethanol solution of tetraethyl orthosilicate is added dropwise over a period of 30 min. After the addition is complete, the reaction continues for 4 h. The mixture is then filtered, washed alternately with deionized water and anhydrous ethanol, and vacuum dried at 80°C for 8 h to obtain the modified conductive ceramic powder. The ratio of the polyaniline-coated conductive ceramic powder to the ethanol solution is 1:25 g / mL; the ethanol solution is composed of anhydrous ethanol and water in a volume ratio of 5:1; the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution is 1:8; and the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is 0.15:1.
[0043] The modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder was pre-irradiated in a nitrogen atmosphere by an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder was transferred to a methanol solution of acrylic acid and reacted at 80°C for 2 hours under nitrogen protection. The mixture was then filtered, washed alternately with methanol and deionized water, and dried under vacuum at 80°C for 8 hours to obtain acrylic acid-grafted polyvinylidene fluoride. The absorbed dose of the pre-irradiation treatment is 60 kGy, and the dose rate is 20 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 25 wt%; the ratio of the pre-irradiated polyvinylidene fluoride powder to the methanol solution of acrylic acid is 1:15 g / mL. B2. The acrylic acid-grafted polyvinylidene fluoride was dissolved in dry N-methylpyrrolidone, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide were added, and the mixture was stirred at room temperature for 60 min under nitrogen protection. p-Nitroaniline was added, and the mixture was reacted at 60 °C for 8 h under nitrogen protection. The reaction solution was dropped into methanol to precipitate the product, filtered, washed with methanol, and dried under vacuum at 80 °C for 8 h to obtain the amidated intermediate product. The ratio of acrylic acid-grafted polyvinylidene fluoride to N-methylpyrrolidone is 1:20 g / mL; the amount of N,N'-dicyclohexylcarbodiimide added is 10 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 5 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 12 wt% of the mass of acrylic acid-grafted polyvinylidene fluoride. B3. The amidation intermediate was dispersed in tetrahydrofuran, hydrazine hydrate was added, and the reaction was carried out at 70°C for 4 h under nitrogen protection. The mixture was filtered, washed alternately with deionized water and ethanol until neutral, and dried under vacuum at 80°C for 12 h to obtain modified polyvinylidene fluoride. The ratio of the amidation intermediate to the tetrahydrofuran is 1:15 g / mL; the mass ratio of the hydrazine hydrate to the amidation intermediate is 2:1.
[0044] A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate includes the following steps: S1. Place the modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate in a mixer and stir at 1000 rpm for 20 minutes at room temperature to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 195°C and 20MPa for 30 minutes. After cooling and demolding, the core layer is obtained. S3. Place the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, and stir and disperse at 800 rpm for 30 min to obtain a conductive anti-corrosion coating slurry. The ratio of the total mass of the modified polyvinylidene fluoride, the modified conductive ceramic powder, and the conductive carbon black to the N-methylpyrrolidone is 1:8 g / mL. S4. The conductive and anti-corrosion coating slurry is uniformly coated on the surface of the core layer with a coating thickness of 250 μm. It is dried at 120°C for 1 hour and then cooled to obtain a highly conductive and corrosion-resistant bipolar lead-acid battery substrate.
[0045] Comparative Example 1 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, mainly differs in that: in step S3 of this comparative example, an equal amount of Ti4O7 is used instead of modified conductive ceramic powder, and in steps S1 and S3, an equal amount of polyvinylidene fluoride is used instead of modified polyvinylidene fluoride. Other components and preparation methods are completely consistent with those in Example 1.
[0046] Comparative Example 2 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, is mainly different in that: in steps S1 and S3 of this comparative example, an equal amount of polyvinylidene fluoride is used instead of modified polyvinylidene fluoride, while the other components and preparation methods are completely consistent with those in Example 1.
[0047] Comparative Example 3 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, mainly differs in that: in step S3 of this comparative example, an equal amount of Ti4O7 is used to replace the modified conductive ceramic powder, while the other components and preparation methods are completely consistent with those in Example 1.
[0048] Comparative Example 4 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, is mainly different in that: in step S3 of this comparative example, an equal amount of surface-activated conductive ceramic powder is used instead of modified conductive ceramic powder, while the other components and preparation methods are completely consistent with those in Example 1.
[0049] Comparative Example 5 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, is mainly different in that: in step S3 of this comparative example, an equal amount of polyaniline-coated conductive ceramic powder is used instead of modified conductive ceramic powder, while the other components and preparation methods are completely consistent with those in Example 1.
[0050] Comparative Example 6 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, mainly differs in that: in steps S1 and S3 of this comparative example, an equal amount of acrylic acid-grafted polyvinylidene fluoride is used instead of modified polyvinylidene fluoride, while other components and preparation methods are completely consistent with those in Example 1.
[0051] Comparative Example 7 A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate, compared with the method for preparing the lead-acid battery substrate in Example 1, is mainly different in that: in step S3 of this comparative example, an equal amount of conductive carbon black is used to replace the modified conductive ceramic powder, while the other components and preparation methods are completely consistent with those in Example 1.
[0052] Performance testing: The highly conductive and corrosion-resistant bipolar lead-acid battery substrates prepared in Examples 1-5 and Comparative Examples 1-7 were cut into samples of specified sizes and subjected to the following relevant performance tests. The test results are shown in Table 1: (1) Volumetric conductivity: The substrate is cut into 50mm×10mm samples with the original thickness of the substrate. Conductive silver paste is coated on both ends of the sample and clamped between the two electrodes. The resistance value R at both ends of the sample is measured at room temperature using a digital multimeter. The volumetric conductivity is calculated according to the formula σ=L / (R×A), where σ is the volumetric conductivity, L is the distance between the two electrodes, R is the measured resistance value, and A is the cross-sectional area of the sample. (2) Weight loss rate of sulfuric acid immersion: The substrate was cut into 25mm×25mm samples, dried in an oven at 80℃ to constant weight, the initial mass m0 was weighed, and the samples were immersed in a sulfuric acid solution with a density of 1.28g / cm³. The samples were then immersed in a constant temperature water bath at 60℃ for 720h. After rinsing with deionized water, the samples were dried in an oven at 80℃ to constant weight, and the mass m1 after immersion was weighed. The weight loss rate of sulfuric acid immersion was calculated according to the formula Δm=(m0-m1) / m0×100%. (3) Coating peel strength: Cut the substrate into 25mm×150mm samples, make a 10mm wide cut on the coating surface with a blade, peel off about 10mm of the coating at one end of the cut from the substrate surface, clamp it on the tensile testing machine fixture, peel off the coating at a peeling speed of 50mm / min along the 90° direction, record the average force during the peeling process, and calculate the peel strength according to the formula P=F / b, where P is the peel strength, F is the peeling force, and b is the peel width; (4) Tensile strength: The substrate is cut into dumbbell-shaped specimens with a total length of 150 mm, a width of 10 mm for the narrow parallel part, and a thickness equal to the original thickness of the substrate. The specimens are stretched at a tensile speed of 5 mm / min on a universal testing machine. The maximum load at which the specimen breaks is recorded. The tensile strength is calculated according to the formula σ = F / A, where σ is the tensile strength, F is the maximum load, and A is the original cross-sectional area of the narrow parallel part of the specimen.
[0053] Table 1
[0054] As can be seen from the test results in Table 1, the substrates prepared in the embodiments of the present invention exhibit excellent performance in terms of volume conductivity, sulfuric acid corrosion resistance, coating peel strength, and tensile strength. Example 3 shows the best overall performance, mainly because under the intermediate process parameters, the silane coupling agent achieves a high degree of surface activation of Ti4O7, polyaniline coating, and silica coating integrity. The grafting, amidation, and nitro reduction of polyvinylidene fluoride are also more complete, resulting in a more perfect conductive network and interface bonding. In Comparative Example 1, because the Ti4O7 and polyvinylidene fluoride used were not modified, the inert surface of Ti4O7 and the interface with polyvinylidene fluoride only exhibit weak van der Waals forces. The conductive filler is unevenly dispersed in the matrix, the conductive pathway is discontinuous, and there is no silica protective layer to physically block sulfuric acid penetration. Sulfuric acid penetrates along the defects at the filler-matrix interface, resulting in the worst performance in all aspects. Comparative Example 2 only modified the ceramic powder. The modified ceramic powder surface has a coupling agent anchoring layer, a polyaniline conductive intermediate layer, and a silica protective layer. The conductivity and corrosion resistance are improved compared to Comparative Example 1. However, because the polyvinylidene fluoride is not functionalized, there is a lack of strong interfacial bonding between the polyvinylidene fluoride and the modified ceramic powder in the coating and the silanol groups on the silica surface, which limits the peel strength of the coating. Comparative Example 3 only modified the polyvinylidene fluoride. The modified polyvinylidene fluoride was enhanced by electron beam pre-irradiation grafting modification, which enhanced the mechanical properties of the matrix itself. However, the unmodified Ti4O7 surface has no chemical anchor points, resulting in poor compatibility with the modified polyvinylidene fluoride. The filler agglomeration leads to an imperfect conductive network, limited interfacial stress transfer efficiency, and the absence of a polyaniline layer and a silica layer to provide corrosion protection. In Comparative Example 4, Ti4O7 was activated only by a silane coupling agent. The coupling agent introduced epoxy groups onto the Ti4O7 surface, which interacted with the amino groups of the modified polyvinylidene fluoride (PVDF) to some extent, improving interfacial compatibility. However, due to the lack of a polyaniline conductive intermediate layer, the contact resistance between Ti4O7 particles and between the particles and the PVDF matrix was relatively high, resulting in limited improvement in conductivity. In Comparative Example 5, Ti4O7 was activated by a coupling agent and coated with polyaniline. The polyaniline layer could be protonated and doped in the sulfuric acid electrolyte to form conductive pathways. Furthermore, the amino groups on the polyaniline chain formed hydrogen bonds with the amino groups of the modified PVDF, resulting in a dense interfacial bond. Both conductivity and peel strength were significantly improved compared to Comparative Example 4. However, due to the lack of a silica outer layer, the polyaniline layer was directly exposed to the sulfuric acid electrolyte. Under the high potential on the positive electrode side, the polyaniline underwent peroxidation degradation, generating benzoquinone-based low-molecular-weight products, resulting in insufficient long-term corrosion resistance. In Comparative Example 6, polyvinylidene fluoride was grafted with acrylic acid to introduce carboxyl groups only after electron beam pre-irradiation. The carboxyl groups formed hydrogen bonds with the silanol groups of the silica layer on the surface of the modified ceramic powder. However, the strength of the hydrogen bonds was weaker than the ionic bonds formed by the amino groups after protonation in the sulfuric acid electrolyte environment with the silanol groups. The interfacial bonding force was insufficient, and the coating peel strength decreased significantly.In Comparative Example 7, conductive carbon black was used to replace modified conductive ceramic powder. Although carbon black can provide a basic electronic conductivity path, it is a particulate random carbon material without the support of Ti4O7's lamellar ceramic skeleton and silicon dioxide protective layer. Furthermore, carbon black undergoes electrochemical oxidation and corrosion at high potentials at the positive electrode, resulting in a significant deterioration in its sulfuric acid resistance.
[0055] This demonstrates that the present invention, through surface activation of Ti4O7 with silane coupling agent, polyaniline coating, and silica coating, and electron beam pre-irradiation grafting with acrylic acid, amidation reaction, and nitro reduction reaction of polyvinylidene fluoride, allows the two modified raw materials to work synergistically in the substrate. The modified conductive ceramic powder provides a conductive network framework and multiple corrosion-resistant protections, and the modified polyvinylidene fluoride forms a strong interfacial chemical bond with the ceramic powder surface through amino groups, significantly improving the conductivity, corrosion resistance, interfacial bonding force, and mechanical strength of the bipolar lead-acid battery substrate.
[0056] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0057] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A highly conductive and corrosion-resistant bipolar lead-acid battery substrate, characterized in that, It includes a core layer and a conductive and corrosion-resistant coating covering the surface of the core layer; The core layer is composed of the following raw materials in parts by weight: 40-60 parts modified polyvinylidene fluoride, 15-30 parts graphite, 10-20 parts conductive carbon black, and 5-10 parts barium sulfate. The conductive anti-corrosion coating is composed of the following raw materials in parts by weight: 30-50 parts modified polyvinylidene fluoride, 20-40 parts modified conductive ceramic powder, and 5-15 parts conductive carbon black. The modified conductive ceramic powder was prepared by surface activation of Ti4O7 with silane coupling agent, polyaniline coating, and silica coating. The modified polyvinylidene fluoride was prepared by grafting acrylic acid onto polyvinylidene fluoride via electron beam pre-irradiation, amidation reaction, and nitro reduction reaction.
2. The high conductivity and corrosion-resistant bipolar lead-acid battery substrate according to claim 1, characterized in that, The modified conductive ceramic powder is prepared by the following steps: A1. Ti4O7 was added to an ethanol solution containing γ-glycidoxypropyltrimethoxysilane, the pH was adjusted to 4-5 with acetic acid, ultrasonically dispersed, stirred and reacted at 50-70℃, filtered, washed and dried to obtain surface-activated conductive ceramic powder. A2. The surface-activated conductive ceramic powder is dispersed in a hydrochloric acid solution containing aniline monomer, ultrasonically dispersed, stirred at 0-5°C, and a hydrochloric acid solution of ammonium persulfate is slowly added dropwise. After the addition is complete, the reaction continues at 0-5°C. The mixture is filtered and washed until neutral to obtain polyaniline-coated conductive ceramic powder. A3. Disperse the polyaniline-coated conductive ceramic powder in an ethanol solution, adjust the pH to 8-9 with ammonia, stir at 40-60°C, and simultaneously add anhydrous ethanol solution of tetraethyl orthosilicate dropwise. After the addition is complete, continue the reaction, filter, wash, and dry to obtain the modified conductive ceramic powder.
3. The highly conductive and corrosion-resistant bipolar lead-acid battery substrate according to claim 2, characterized in that, In step A1, the ethanol solution containing γ-glycidoxypropyltrimethoxysilane has a mass fraction of 1-3 wt% for γ-glycidoxypropyltrimethoxysilane.
4. The highly conductive and corrosion-resistant bipolar lead-acid battery substrate according to claim 2, characterized in that, In step A2, the concentration of aniline monomer in the hydrochloric acid solution containing aniline monomer is 0.05-0.2 mol / L, and the concentration of hydrochloric acid is 0.8-1.2 mol / L; the concentration of ammonium persulfate in the hydrochloric acid solution is 0.05-0.2 mol / L; and the molar ratio of ammonium persulfate to aniline is (0.8~1):
1.
5. The highly conductive and corrosion-resistant bipolar lead-acid battery substrate according to claim 2, characterized in that, In step A3, the volume ratio of tetraethyl orthosilicate to anhydrous ethanol in the anhydrous ethanol solution of tetraethyl orthosilicate is 1:(3~8); the mass ratio of tetraethyl orthosilicate to the polyaniline-coated conductive ceramic powder is (0.05~0.15):
1.
6. The high conductivity and corrosion-resistant bipolar lead-acid battery substrate according to claim 1, characterized in that, The modified polyvinylidene fluoride is prepared by the following steps: B1. Polyvinylidene fluoride powder was pre-irradiated in a nitrogen atmosphere by an electron accelerator. After irradiation, the pre-irradiated polyvinylidene fluoride powder was transferred to a methanol solution of acrylic acid and reacted at 60-80℃ under nitrogen protection. The mixture was then filtered, washed, and dried to obtain acrylic acid-grafted polyvinylidene fluoride. B2. The acrylic acid-grafted polyvinylidene fluoride was dissolved in dry N-methylpyrrolidone, N,N'-dicyclohexylcarbodiimide and N-hydroxysuccinimide were added, and the mixture was stirred at room temperature under nitrogen protection. p-Nitroaniline was added, and the mixture was reacted at 40-60°C under nitrogen protection. The reaction solution was dropped into methanol to precipitate the product, filtered, washed, and dried to obtain the amidated intermediate. B3. Disperse the amidation intermediate in tetrahydrofuran, add hydrazine hydrate, react at 50-70°C under nitrogen protection, filter, wash until neutral, and dry to obtain modified polyvinylidene fluoride.
7. The highly conductive and corrosion-resistant bipolar lead-acid battery substrate according to claim 6, characterized in that, In step B1, the absorbed dose of the pre-irradiation treatment is 40-60 kGy, and the dose rate is 5-20 kGy / s; the mass fraction of acrylic acid in the methanol solution of acrylic acid is 15-25 wt%.
8. The highly conductive and corrosion-resistant bipolar lead-acid battery substrate according to claim 6, characterized in that, In step B2, the amount of N,N'-dicyclohexylcarbodiimide added is 2-10 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, the amount of N-hydroxysuccinimide added is 1-5 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride, and the amount of p-nitroaniline added is 3-12 wt% of the mass of the acrylic acid-grafted polyvinylidene fluoride.
9. The high conductivity and corrosion-resistant bipolar lead-acid battery substrate according to claim 6, characterized in that, In step B3, the mass ratio of the hydrazine hydrate to the amidation intermediate is (0.5~2):
1.
10. A method for preparing a highly conductive and corrosion-resistant bipolar lead-acid battery substrate as described in any one of claims 1-9, characterized in that, Includes the following steps: S1. Place the modified polyvinylidene fluoride, graphite, conductive carbon black, and barium sulfate in a mixer and stir and mix at room temperature for 20-40 minutes to obtain a mixed powder. S2. Place the mixed powder in a mold and hot-press it at 180-195℃ and 10-20MPa for 30-60 minutes. After cooling and demolding, the core layer is obtained. S3. Place the modified polyvinylidene fluoride, modified conductive ceramic powder, and conductive carbon black in a container, add N-methylpyrrolidone, and stir and disperse for 30-60 minutes to obtain a conductive anti-corrosion coating slurry. S4. The conductive anti-corrosion coating slurry is uniformly coated on the surface of the core layer with a coating thickness of 100-250μm. It is dried at 80-120℃ for 1-3h to form a conductive anti-corrosion coating on the surface of the core layer. After cooling, a highly conductive and corrosion-resistant bipolar lead-acid battery substrate is obtained.